“IN IMPROVING CONSUMER DECISIONS CHOOSE SHOPPING AT INDOMARKET MINIMARKET BY UPGRADE QUALITY OF SERVICE AND THE INFLUENCE OF REFERENCE GROUP“ - Suganda, Uce Karna; Syaifullah, Ilham; Malini, Sani; Sinaga, Obsatar (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research is based on the growth rate of minimarket in Bandung.This of course will affect the number of people who shop in the modern market or minimarket.Shopping service providers must prepare the best strategy to attract consumers, because with the emergence of new outlets the consumer becomes increasingly have many choices. Minimarket Indomaret In Bandung is one of the outlets affected by the imbalance.Can be seen from the number of outlets between rivals Indomart The problem in this study is "what factors influence a person's decision to choose to shop at Indomaret".Specifically focused on two variables: service quality and reference group.The purpose of this study is to be able to study the influence of these two variables in influencing consumer decisions in choosing to shop at Indomaret. Population in this research is minimarket consumer Indomaret.The samples used in the study of 100 consumers randomly, using the method of accidental sampling with random sampling approach.Methods of data collection using questionnaires.Data analysis using descriptive analysis of the percentage and multiple linear regression analysis. Based on the result of research, it is known that there is influence of service quality and reference group to consumer decision.Simultaneously influence of service quality and trust to the satisfaction of inpatient patient based on F test obtained value 11.776.This research concludes service quality and reference group have positive and significant influence to consumer decision in choosing shopping at Indomaret.